Adult Education and Public Engagement: The "Social Inclusion and Community Well-Being" project - Chiara Biasin (Firenze University Press, 2024)
Public engagement is an important part of the third mission of universities. It is a form of governance aimed at innovation and development in the territories. It involves a wide audience in informing, collaborating, and disseminating research as a public good. Adult education is widely recognised to play a crucial role in society by engaging citizens in proposals, reflections, and educational practices to develop the knowledge and skills necessary to form more active, participating, and democratic communities. The "Social Inclusion and Community Well-being" project, as a form of public engagement according to a participatory and collaborative research approach, and networked with the territory, intends to integrate these two orientations. The project aims to promote the social inclusion among adults in situation of personal and social vulnerability, improve the well-being of local communities, and ensure training to service providers.   Educazione degli adulti e Public Engagement: il progetto "Inclusione Sociale e Benessere delle Comunità". Il public engagement è una parte importante della terza missione delle università. È una forma della governance che mira all'innovazione e allo sviluppo dei territori. Coinvolge un vasto pubblico nell'informazione, nella collaborazione e nella disseminazione della ricerca intesa come pubblico bene. L'educazione degli adulti è ampiamente riconosciuta per il ruolo cruciale che svolge nella società impegnando i cittadini in proposte, riflessioni e pratiche educative per lo sviluppo di conoscenze e competenze necessarie a formare comunità più attive, partecipi e democratiche. Il progetto "Inclusione Sociale e Benessere della Comunità", come forma di public engagement, secondo un approccio di ricerca partecipativa, collaborativa, e in rete con il territorio, intende integrare questi due orientamenti. Il progetto mira a promuovere l'inclusione sociale di adulti in situazioni di vulnerabilità personale e sociale, migliora il benessere delle comunità locali e garantisce la formazione degli operatori dei servizi.